Accountability of Corporate Criminal Implementation for the Defendant of Character Assassination Acts - Jesslyn Elisandra Harefa; Yasmirah Mandasari Saragih; Bonari Tua Silalahi; Ireny Natalia Putri Sihite; Sudarno Hariadi Nasution (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The phenomenon of character assassination is now increasingly prevalent in the digital realm, often carried out by corporate entities through destructive information campaigns. Unfortunately, the criminal law system in Indonesia has not been fully able to provide strict accountability for legal entities. This research aims to analyze how criminal accountability can be applied to corporations involved in character assassination. The research method used is a normative juridical approach with qualitative analysis techniques of relevant regulations and case studies. The results of the study show that there is a void of norms in Indonesian criminal law related to corporate criminal liability in non-physical cases such as digital defamation.